Highly-ordered maghemite/reduced graphene oxide nanocomposites for high-performance photoelectrochemical water splitting. Issue 37 (25th March 2015) - Chandrasekaran, Sundaram; Hur, Seung Hyun; Kim, Eui Jung; Rajagopalan, Balasubramaniyan; Babu, Kadumudi Firoz; Senthilkumar, Velusamy; Chung, Jin Suk; Choi, Won Mook; Kim, Yong Soo
Abstract : Highly ordered γ-Fe2 O3 /reduced graphene oxide (RGO) was synthesized via a facile solution technique combined with calcination at various temperatures. Abstract : Highly ordered γ-Fe2 O3 /reduced graphene oxide (RGO) was synthesized via a facile solution technique combined with calcination at various temperatures. The maghemite iron oxide structure was obtained on the GO surface and improved crystallinity of γ-Fe2 O3 was observed as the calcination temperature increased. The prepared highly ordered maghemite structure on RGO exhibited an excellent water splitting performance under UV light (∼360 nm) illumination. The photocurrent density of RGO/γ-Fe2 O3 calcined at 500 °C was 6.74 mA cm −2 vs. RHE and a high incident photon to current conversion efficiency (IPCE) of 4.7%, was achieved. This photocurrent density and the IPCE values are 3.7 times and 4 times higher than that of pristine iron oxide, respectively.